Obstacles of Field Agricultural Extension In Socializing the Program to Corn Farmer Groups in Teon Nila Serua District, Central Maluku Regency - Frijer Lodarmase; R.A. Far far; P.M. Puttileihalat (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine the constraints of agricultural extension workers in socializing the program to corn farmer groups in Teon Nila Serua District, Central Maluku Regency. This study uses a purposive sampling technique, namely the selection of samples based on certain characteristics with records of people who understand the real problems and conditions in the field. One way is through in-depth interviews from one informant to another and so on. The results showed that the obstacles faced by agricultural extension workers in Teon Nila Serua District in socializing the program included farmer participation, distance, time, and facilities and infrastructure. Each member is expected to participate in every group meeting, the goal is that members can obtain solutions to the problems they face